2022
DOI: 10.3389/fmed.2022.1017371
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of electrical stimulation for lower-extremity muscle weakness in intensive care unit 2019 Novel Coronavirus patients: A phase I double-blinded randomized controlled trial

Abstract: BackgroundIntensive care unit (ICU) prolonged immobilization may lead to lower-extremity muscle deconditioning among critically ill patients, particularly more accentuated in those with 2019 Novel Coronavirus (COVID-19) infection. Electrical stimulation (E-Stim) is known to improve musculoskeletal outcomes. This phase I double-blinded randomized controlled trial examined the safety and efficacy of lower-extremity E-Stim to prevent muscle deconditioning.MethodsCritically ill COVID-19 patients admitted to the IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…This suggests that only the intervention group regained muscle endurance as a response to E-Stim therapy. Our results are also in line with our previous study, which reported improved muscle endurance in response to lower extremity E-Stim therapy (Zulbaran-Rojas et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests that only the intervention group regained muscle endurance as a response to E-Stim therapy. Our results are also in line with our previous study, which reported improved muscle endurance in response to lower extremity E-Stim therapy (Zulbaran-Rojas et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…An additional objective measure to assess the improvement in muscle endurance is through iEMG analysis (Zulbaran‐Rojas et al, 2022), which reflects increased muscle fiber activation (Cettolo et al, 2007). In our overall cohort, at baseline, we observed a decline in muscle endurance during the 1 h E‐Stim session (Figure 4a), which was expected given the impaired oxygen metabolism seen in PASC patients, leading to faster muscle fatigue (Nosaka et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few studies of the effects of EMS therapy in patients with COVID-19. In a previous RCT, application of EMS to the gastrocnemius muscles for up to 14 days was accompanied only by improvements in lower extremity muscle condition, e.g., ankle muscle strength and endurance, in critically ill patients with COVID-19 admitted to the ICU 30 . In another study, application of EMS to the quadriceps femoris muscles for 7 consecutive days only increased muscle strength assessed according to the MRC score and function in patients with severe COVID-19 during ICU admission, although they did not include a control group for comparison 31 .…”
Section: Discussionmentioning
confidence: 91%
“…More than half of the studies (57%, N=30, 2075 participants) included adults with PCC, 42 - 46 , 48 - 51 , 53 , 56 , 57 , 59 - 62 , 64 , 66 , 67 , 70 - 72 , 74 - 76 , 81 , 83 , 85 , 88 , 89 followed by adults with non-severe (34%, N.=18, 1489 participants), severe (6%, N.=3, 230 participants) 39 , 63 , 86 and critical COVID-19 (4%, N.=2, 88 participants). 41 , 90 …”
Section: Evidence Synthesismentioning
confidence: 99%